Role of Hole Injection in Electroforming of LiF-Polymer Memory Diodes - Bory, B. F. (2015)
Al/LiF/poly(spirofluorene)/Ba/Al diodes submitted to bias voltages near 15 V undergo a change to a nonvolatile memory known as electroforming. Prior to electroforming, electron trapping occurs, followed by a tunneling current due to electrons from the polymer into LiF. At the onset voltage for electroforming, a sudden electroluminescence burst originating from electronic excitations in the polymer is detected. This confirms that hole injection into the polymer through LiF occurs leading to nonvolatile resistive switching.